'BETTER OFF DEAD THAN DISFIGURED'? THE CHALLENGES OF FACIAL INJURY IN THE PRE-MODERN PAST. (29th September 2016) - Skinner, Patricia
ABSTRACT: This paper argues that facial disfigurement has been neglected in the historiography of medieval Europe, and suggests some reasons for this oversight before examining the evidence from legal and narrative texts. One reason for this may be the lack of first-person accounts of being disfigured, preventing historians from accessing the experience of being disfigured. By situating the medieval examples within a wider frame of modern responses to disfigurement, it becomes apparent that whilst medical advances have assisted in restoring the damaged face, social responses to facial difference remain largely negative.